1986
DOI: 10.1002/hep.1840060522
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous expression of phenobarbital-inducible cytochrome P-450 genes within the hepatic acinus in the rat

Abstract: Within the hepatic acinus, the functional unit of liver parenchyma, the induction of cytochrome P-450 protein by phenobarbital is manifested primarily in hepatocytes located closer to the hepatic venule, i.e., distal hepatocytes. The objective of this study was to determine the levels of cytochromes P-450b and P-450e mRNAs in populations of hepatocytes originating in the proximal or distal half of the liver acinus in the rat, as an approach to the elucidation of the mechanisms responsible for the heterogeneous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

1987
1987
1993
1993

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 25 publications
1
13
0
Order By: Relevance
“…To begin to understand the factors that might contribute to the liver developmental program, a number of laboratories have begun to use molecular probes to study the patterns of expression of specific genes under various circumstances, e.g., during normal development (SalaTrepat et al 1979;Liao et al 1980;Tilghman and Belayew 1982;Meeham et al 1984;Powell et al 1984;Sellem et al 1984;Giachielli and Omiecinski 1986;Poliard et al 1986), during liver regeneraton Tamaoki and Fausto 1984;Panduro et al 1986), in different regions of the hepatic lobule (Chianale et al 1986), in isolated hepatocytes (Clayton and Darnell 1983;Jefferson et al 1984;Jefferson et al 1985), and in various hepatoma cell lines, variants, and somatic cell hybrids (Peterson and Weiss 1972;Darlington et al 1974;Peterson 1976;Clayton et al 1985b). Most of these studies have been limited to analysis of steady-state levels of one or a few related mRNAs under a variety of circumstances.…”
Section: Discussionmentioning
confidence: 99%
“…To begin to understand the factors that might contribute to the liver developmental program, a number of laboratories have begun to use molecular probes to study the patterns of expression of specific genes under various circumstances, e.g., during normal development (SalaTrepat et al 1979;Liao et al 1980;Tilghman and Belayew 1982;Meeham et al 1984;Powell et al 1984;Sellem et al 1984;Giachielli and Omiecinski 1986;Poliard et al 1986), during liver regeneraton Tamaoki and Fausto 1984;Panduro et al 1986), in different regions of the hepatic lobule (Chianale et al 1986), in isolated hepatocytes (Clayton and Darnell 1983;Jefferson et al 1984;Jefferson et al 1985), and in various hepatoma cell lines, variants, and somatic cell hybrids (Peterson and Weiss 1972;Darlington et al 1974;Peterson 1976;Clayton et al 1985b). Most of these studies have been limited to analysis of steady-state levels of one or a few related mRNAs under a variety of circumstances.…”
Section: Discussionmentioning
confidence: 99%
“…15 M NaCl. Previous studies in this laboratory have shown that the maximal induction of total cytochrome P-450 activity, assessed spectrophotometrically, is achieved by -33 h after a single dose of PB (9). Therefore, 33 h after a single dose of PB, snap-frozen pieces of liver were sectioned at 6 um in a cryostat.…”
Section: Hybridization Conditionsmentioning
confidence: 99%
“…shown (5,9). To assess whether pOHPB would induce these P-450 genes if administered in various doses, this drug was given as three daily doses of400 mg/kg, i.p.…”
Section: Quantitative Assessmentmentioning
confidence: 99%
See 2 more Smart Citations